Gestión de riesgos laborales en la construcción de pozos de revisión de una constructora en la parroquia de San Andrés, cantón Guano, provincia de Chimborazo. - Pacheco Sánchez, Mario Roberto (2024)
The research titled “Occupational Risk Management in the Construction of Manholes for a Construction Company in the Parish of San Andrés, Guano Canton, Chimborazo Province,” aimed to manage the risks to which the workers of the JVM Consortium are exposed. For this purpose, the risks associated with the construction process were identified, measured, and evaluated, followed by the development of comprehensive operational control. Initially, a situational diagnosis was carried out, followed by the identification and evaluation of risks, which was developed using the NTP 330 methodology: a simplified system for accident risk assessment, correlating deficiency, exposure, probability, and consequence levels. Additionally, workplace noise measurement was considered using an analyzer dosimeter and its subsequent evaluation through the Method of Evaluation and Prevention of Risks related to workers' exposure to noise issued by the INSST of Spain. As a result of the evaluation, it was determined that 13.64% of the risks belong to intervention level "I," 51.51% correspond to intervention level "II," and finally, 34.85% are associated with intervention level "III." Regarding the measurement and evaluation of noise, it was concluded that in the four analyzed workstations, the permissible exposure level [85 dB (A)] is exceeded; however, workers use their hearing protectors, which, according to calculations and the octave band method, provide an effective attenuation of 21 dB.